2015
DOI: 10.5530/pc.2015.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of aqueous extracts from Crataegus oxyacantha leaves

Abstract: Background: Crataegus (Rosaceae) genus comprises more than 200 species worldwide but few species have been used medicinally. In the Mediterranean region, the predominant species of this genus is C. oxyacantha syn. Monogyna (known as Hawthorn) which is protective against the treatment of mild heart diseases. Methods: The leaves were collected at three different stages (vegetative, flowering and fruiting). The aim of this work was to determine total phenol, flavonoid, flavon and flavonol contents, as well as ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…Similarly, the IC 50 values are in the order of 1.86 ± 0.01 mg/mL and 9.23 ± 0.01 mg/mL for ascorbic acid, and C monogyna , respectively. Our results demonstrated that the aqueous extract of C monogyna had less radical trapping activity than the ethanolic extract of IC 50 leaves (22.5 µg/mL) found by Fouzia et al 31 Furthermore, Amor and Belhattab 39 reported an IC 50 of C monogyna aqueous leaf extract ranging from 45 to 725 µg/mL at different vegetation stages. Coimbra et al 40 reported that the extracts obtained from C monogyna demonstrated an IC 50 value of 36.11 g/mL.…”
Section: Resultssupporting
confidence: 40%
“…Similarly, the IC 50 values are in the order of 1.86 ± 0.01 mg/mL and 9.23 ± 0.01 mg/mL for ascorbic acid, and C monogyna , respectively. Our results demonstrated that the aqueous extract of C monogyna had less radical trapping activity than the ethanolic extract of IC 50 leaves (22.5 µg/mL) found by Fouzia et al 31 Furthermore, Amor and Belhattab 39 reported an IC 50 of C monogyna aqueous leaf extract ranging from 45 to 725 µg/mL at different vegetation stages. Coimbra et al 40 reported that the extracts obtained from C monogyna demonstrated an IC 50 value of 36.11 g/mL.…”
Section: Resultssupporting
confidence: 40%